2021
DOI: 10.1002/jemt.23702
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning techniques to detect and forecast the daily total COVID‐19 infected and deaths cases under different lockdown types

Abstract: COVID‐19 has impacted the world in many ways, including loss of lives, economic downturn and social isolation. COVID‐19 was emerged due to the SARS‐CoV‐2 that is highly infectious pandemic. Every country tried to control the COVID‐19 spread by imposing different types of lockdowns. Therefore, there is an urgent need to forecast the daily confirmed infected cases and deaths in different types of lockdown to select the most appropriate lockdown strategies to control the intensity of this pandemic and reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…Their results suggest that these predictors are relevant for COVID-19 mortality rate modelling. Similar to our work, Saba et al [16] implemented multiple machine learning models to forecast COVID-19 cases based on NPI implementation. However, their work differs in that it only includes lockdown type as an NPI feature (and does not consider cultural dimensions), the study is limited to 9 countries, and the reported case numbers are predicted instead of the change in case numbers.…”
Section: Related Workmentioning
confidence: 98%
See 3 more Smart Citations
“…Their results suggest that these predictors are relevant for COVID-19 mortality rate modelling. Similar to our work, Saba et al [16] implemented multiple machine learning models to forecast COVID-19 cases based on NPI implementation. However, their work differs in that it only includes lockdown type as an NPI feature (and does not consider cultural dimensions), the study is limited to 9 countries, and the reported case numbers are predicted instead of the change in case numbers.…”
Section: Related Workmentioning
confidence: 98%
“…Machine learning has been used in applications to combat the COVID-19 pandemic, such as in patient monitoring and genome sequencing [63][64][65][66]. Recent studies have also used various statistical and machine learning techniques for short-term forecasting of infection rates for the COVID-19 pandemic [13,15,16,30,33] using reported transmission and mortality statistics, population geographical movement data, and media activity. Pinter et al [13] combined multilayer perceptron with fuzzy inference to predict reported infection and mortality numbers in Hungary with only case number features from May to August 2020.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Other well-known algorithms have been tested, such as ARIMA (auto-regressive integrated moving average model) [66] and support vector machine (SVM), which are mainly used for the forecasting of time series data [67,68]. Several of these models have been applied as predictors of daily infections under different types of lockdown, thus helping in government decision making [69,70]. ML techniques have been successfully used to plan public policies [71].…”
Section: Artificial Intelligence Applied To Large-scale Covid-19 Management Public Policies (Dark Blue Cluster)mentioning
confidence: 99%